Acetoclastic archaea adaptation under increasing temperature in lake sediments and wetland soils from Alaska - Dellagnezze, B. M.; Bovio-Winkler, P.; Lavergne, C.; Menoni, D. A.; Mosquillo, F.; /Cabrol, Léa; Barret, M.; Etchebehere, C. (2023)
The activity of methanogenic archaea is expected to be strongly affected under warmer temperatures, with higher greenhouse gas (GHG) emissions in the Arctic. In the sub-Arctic and Arctic freshwater sediments and wetland soils, acetoclastic methanogenesis is one of the major processes involved in methane (CH4) release. To investigate the microbial adaptation/ tolerance at warmer temperatures and high acetate concentration, anaerobic microcosms of lake sediments and wetland soils from sub-Arctic ecosystems from Denali to Toolik regions in Alaska (USA) were set up at four temperatures (5, 10, 15 and 20 degrees C). In both environmental and microcosm samples, archaeal diversity was evaluated through specific archaeal 16S rRNA sequencing as well as bacterial, archaeal and methanogen abundance using quantitative PCR. Acetate amendment strongly modified the archaeal diversity highly favoring methanogens from Methanosarcinales, and in lower abundance, Methanoregula and Bathyarchaeia in some lake sediment. While acetoclastic groups significantly diverged among aquatic and terrestrial ecosystems, temperature did not significantly shape methanogens' diversity, showing their adaptability under warmer conditions. Faster microbial response on CH4 production rates was observed at warmer temperatures (15 and 20 degrees C), bringing insights on the psychrophilic acetoclastic groups adapted to high acetate concentration with potential biotechnological application.